(untitled) (Italian Journal of Public Health, 2012)
The modern health system of Argentina was developed in 1945-1955, a period of economic bonanza characterized by industrialization, rapid urbanization and activist labor organizations. During the ensuing years it evolved in three sectors: public, social security and private, with separate services, population coverage and funding. While the national Ministry of Health is nominally responsible for general health policies and regulations, overseeing the general operation of health services, designing preventive medicine programs and negotiating the coverage and fees of health insurance plans, it has in fact very low leverage to enforce decisions in the provinces, which are autonomous, as well as in the social security and private sectors, which are weakly regulated if at all. While the health workforce, medical facilities and level of spending are acceptable, the fragmentation and segmentation of the system render it highly inequitable and inefficient. During the 1980s and 1990s, the health system has experienced further transformations, as neoliberal policies took hold in the country and dictated a reduction of state involvement in social services in favor of privatization and decentralization of health care. The result has been increased fragmentation, inequity and inefficacy, as health care is increasingly prey to the economic interests of private corporations (insurance and pharmaceutical industries), trade union bureaucracies and the medical professional and technology establishments. The expectation of popular sectors of society are that progressive polices recently enacted by Congress, and being implemented in the fields of education, retirement pensions and the media, will be followed with much needed public health policies based on equity and efficiency.